Satoyoshi Syndrome: Difficult to find or treat? - Majumder, Ashik; Das, Aditi; Bhowmick, Rohit; Bhunia, Niladri Sekhar; Sarkar, Subhankar; Sonowal, Rimjhim (Indian Journal of Child Health, 2025)
Satoyoshi Syndrome, also known as Komuragaeri disease, is a rare multisystemic autoimmune disorder characterised by alopecia, intermittent painful muscle spasms, diarrhoea, endocrinopathies, skeletal deformities, and positivity for antinuclear antibodies (ANA). The etiology of this condition remains unclear. This case report discusses Satoyoshi Syndrome in a 10-year-old girl, emphasising the diagnostic challenge, clinical course, treatments, and outcomes.